AN ANALYSIS OF SYMBOLISM IN TENNESSEE WILLIAMS’ PLAY THE GLASS MENAGERIE - Eka Siswantara (Universitas Negeri Manado, 2023)
This research entitled Ã¢â‚¬Å“An Analysis of Symbolism in Tennessee WilliamsÃ¢â‚¬â„¢ Play The Glass MenagerieÃ¢â‚¬Â aims at understanding the meaning of each symbol in the play. The data of this research were obtained from the script of the play as the primary data and the secondary data were gained from several references from books and articles to support the analysis. The method of analyzing the data used was objective approach focusing on the intrinsic element of the play. Based on the discussion, the writer concludes that the symbols in this play are implied within three elements, they are (1) Symbol in the characters, where several objects are employed to symbolize and emphasize the characteristics and certain idea of the character in the play. Here several objects such as the glass menagerie, Victrola, blue roses and the glass unicorn represent the characteristic and certain idea within Laura Wingfield, meanwhile certain characteristic and theme in Tom Wingfield are represented through a fire escape, movies, merchant marine, and some other symbols attached to him. Certain objects also significantly become the symbol for certain idea in the other characters. (2) Symbol in the action of the character, where the actions of the character in this play symbolically imply certain idea to emphasize and clarify the story of the play. (3) Symbol in the background and setting, where certain place and moment are presented as the symbol for certain idea and issue in this play.